Q: Y equals 10x - 9 y equals x plus 18?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

0

x = 4

5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

Substitute the values of x and y in 10x + 7y, thus: 10x + 7y = 10*9 + 7*6 = 90 + 42 = 132

Related questions

0

x2 + 9 = 10x x2 - 10x + 9 = 0. (x - 9)(x - 1) = 0. Therefore, x = 1 or 9.

5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8

x = 4

-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1

Substitute the values of x and y in 10x + 7y, thus: 10x + 7y = 10*9 + 7*6 = 90 + 42 = 132

10x + -9 = 59can be rewritten as10x - 9 = 59add 9 to both sides10x = 68divide both sides by 10x = 6.8

16x - 10x + 9 = 99 - 30 6x + 9 = 69 so 6x = 60 or x = 10

7x+3=10x-9(shift +3 & 10x) 7x-10x=-9-3(signs changed) -3x=-12(divide both sides by -3) x=4

12x + 9 = 10x + 1 Subtract 10x from both sides: 2x + 9 = 1 Sutract 9 from both sides: 2x = - 8 Divide both sides by 2: x = -4

18

9 degrees